Desire to Be Liked and Exist in Mass Communication - Yalçınkaya, Ece Nur; Özpolat, Kainat (IGI Global Scientific Publishing, 2026)
Since the beginning of life on earth, living beings have managed to communicate with each other in some way. The most notable of these creatures is humans. Humans, who have the ability to speak, have developed various communication skills in order to reach other people with whom they share a common life. Over time, verbal communication has developed and given way to communication methods. The internet and social media, which have developed along with the internet, have also made a great contribution to the communication adventure. Mass media, which have shown themselves in many areas of our lives, have not only strengthened the communication environment, but have also managed to play a leading role in many areas such as information exchange, entertainment or education. The most prominent of mass media are social media platforms. Social media platforms have also brought with them a number of problems. Copyright © 2026, IGI Global Scientific Publishing.
Keywords: Beginning Of Lives; Communication Environments; Communication Method; Communication Skills; Internet Media; Mass Communication; Mass Media; Social Media; Social Media Platforms; Verbal Communications; Social Networking (Online)